Design and optimization of cost-effective coldproof portable enclosures for polar environment - Behzad Parsi; Lihong Zhang (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Based on the International Electrotechnical Commission standards, the electronic devices in the industrial class (e.g., integrated circuits or batteries) can only operate at the ambient temperature between -40°C and 85°C. For the human-involved regions in Alaska, Northern Canada, and Antarctica, extreme cold condition as low as -55°C might affect sensing electronic devices utilized in the scientific or industrial applications. In this paper, we propose a design and optimization methodology for the self-heating portable enclosures, which can warm up the inner space from -55°C for encasing the low-cost industrial-class electronic devices instead of expensive military-class ones to work reliably within their allowed operating temperature limit. Among the other options, ceramic thermal resistors are selected as the heating elements inside the enclosure. The placement of the thermal resistors is studied with the aid of thermal modelling for the single heating device by using the curve fitting technique to achieve uniform temperature distribution within the enclosure. To maintain the inner temperature above -40°C but with the least power consumption from the thermal resistors, we have developed a control system based on the fuzzy logic controller. For validation, we have utilized COMSOL Multiphysics software and then one prototyped enclosure along with the fuzzy control system. Our experimental measurement exhibits its efficacy compared to the other design options.